Effect of Process Temperature and Time on the Properties of Microwave Plasma Nitrided Ti6Al4V alloy - Yusuf, Yusliza; Mohamad Juoi, Jariah; Mohd. Rosli, Zulkifli; Kwan, Wai Loon; Mahamud, Zainab (Universiti Putra Malaysia Press, 2013)
Titanium alloy (e.g. Ti-6Al-4V) has an excellent combination of properties. However in many cases, the application is limited because of the poor wear property. In this work, a surface modification (plasma nitriding) is carried out to improve the surface properties of Ti-6Al-4V, as a treatment prior to a hardcoating deposition, leading to a duplex coating system. This is an effort to improve the surface and near surface property of Ti-6Al-4V. Plasma nitriding is performed utilizing microwave plasma method in 25% Ar- 75% N2 atmosphere at temperatures of 600°C and 700°C for different processing times (1, 3 and 5 hours). The phase and microstructure of plasma nitrided substrate were characterized by using X-ray diffraction (XRD) and Scanning electron microscopy (SEM). The plasma nitrided Ti-6Al-4V properties (surface roughness, surface hardness and case depth) were determined using profilometer and microhardness, respectively. Results obtained showed a significant increase on the surface hardness of Ti-6Al-4V. This is due to the formation of TiN and Ti2N phases in the form of compound layer. Besides, it shows that the diffusion of nitrogen into the Ti-6Al-4V substrate produces case depth up to 130 μm and this contributes to the improvement of the near surface hardness due to the changes in the microstructures. It was also found that the surface hardness and surface roughness increased with the increases in the process temperature and times.